The Important Role Of Artificial Intelligence Regulation In Protecting Public Interest - Francisca Romana Nanik Alfiani; Faisal Santiago (Journal Of Social Science (JoSS), 2024)
Artificial intelligence provides both good and evil. For this reason, artificial intelligence must be regulated to protect the public interest. The research results show that regulating artificial intelligence is not easy, it is very complicated, and there are many challenges, especially as the development of artificial intelligence technology is very rapid while the law is slow to anticipate it. By 2022, globally, there will be 37 regulations governing artificial intelligence. From the results of the comparison of various best practices and regulations from other countries leading in the field of artificial intelligence, such as the European Union, China, and the United States framework approach, it can be used as input for developing artificial intelligence regulations in Indonesia that guarantee the use of artificial intelligence responsibly, respecting values. humanity, and does not hinder the creation of an artificial intelligence development ecosystem.